An Analysis of Dysphemism Uttered by the Main Characters in Bottoms (2023) Film - Alfiansyah, Riska Amelia; Arifin, M. Bahri (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
Communication was the foundation of human interaction through language, and sociolinguistics studied how language worked in society, including how speakers employed dysphemism to express social identity, emotion, or intention through harsh or offensive language choices in specific contexts. This research examined the dysphemism expressions uttered by PJ and Josie as the main characters in Bottoms (2023) film, using the theory from Allan and Burridge (1991) to identify eight types of dysphemism and to describe the seven motives of dysphemism used in the main characters’ utterances. This research used a qualitative descriptive method to display and analyze the data, and found a total of 76 data in the main characters’ utterances. There were only five types of dysphemism identified within the characters’ sentences: obscenity with 54 data, dysphemistic epithets with 14 data, profanity with 3 data, “-ist” dysphemism with 3 data, and dysphemistic euphemism with 2 data. On the other hand, there were only six motives: to humiliate with 11 data, to express strong emotion with 26 data, to emphasize with 18 data, to state a bad situation with 7 data, to show astonishment with 8 data, and to create humor/show intimacy with 6 data. The findings revealed that dysphemistic expressions used by the main characters were not solely intended to insult but served a variety of communicative purposes, with expressing anger and adding emphasis being the dominant motives. The main characters’ utterances illustrated how dysphemism worked with diverse motives in casual conversations, highlighting its role beyond mere offense to expressing emotion.